Nanosilicon: An approach for abiotic stress mitigation and sustainable agriculture - Verma, Krishan K.; Zeng, Yuan; Song, Xiu-Peng; Singh, Munna; Wu, Kai-Chao; Rajput, Vishnu D.; Li, Yang-Rui (Frontiers in Plant Science, 2022)
Abiotic stresses cause extensive yield loss in various crops globally. Over the past few decades, the application of silicon nanoparticles (nSi) has emerged as an abiotic stress mitigator. The initial responses of plants are exemplified by the biogenesis of reactive oxygen species (ROS) to sustain cellular/organellar integrity, ensuring in vivo operation of metabolic functions by regulating physiological and biochemical pathways during stress conditions. Plants have evolved various antioxidative systems to balance/maintain the process of homeostasis via enzymatic and non-enzymatic activities that repair any losses. In an adverse environment, supplementation of Si mitigates the stress condition and improves the growth and development of plants. Its ameliorative effects are correlated with enhanced antioxidant enzymes activities, maintaining the equilibrium between ROS generation and reduction. However, a limited number of studies cover the role of nSi in abiotic stress conditions. This review addresses the accumulation and/or uptake of nSi in several crops, as well as its mode of action, which are linked with improved plant growth and tolerance capabilities, contributing to sustainable agriculture.